GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 17293 species occurrences available in GBIF matching the query: Country: Guam. The dataset includes 17293 records from 150 constituent datasets: 5 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Porifera. 4 records from Western Australian Museum provider for OZCAM. 3 records from UCBG TAPIR Provider. 1 records from Herbario Museo de La Salle Bogotá (MLS). 83 records from Paleobiology Database. 33 records from iNaturalist research-grade observations. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 322 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 70 records from Macaulay Library Audio and Video Collection. 43 records from Essig Museum of Entomology. 10 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 91 records from Academy of Natural Sciences OBIS Mollusc Database. 1 records from TTU Mammals Collection. 1 records from CABI Bioscience Fungus Collection. 4 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 28 records from KUBI Ichthyology Collection. 619 records from Bishop Museum Natural Sciences Data. 23 records from Missouri Botanical Garden. 1 records from Field Museum of Natural History (Botany) Bryophyte Collection. 10 records from Collection Aves (bird skins) SMF. 4 records from Museum of Zoology, University of Navarra. 49 records from Herbarium of The New York Botanical Garden. 3 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 9 records from CONN. 4 records from Herps Specimens. 20 records from Royal Botanic Garden Edinburgh Herbarium (E). 2 records from UMMZ Birds Collection. 17 records from UF FLMNH Ichthyology. 1 records from UCM Mammals Collection. 24 records from Harvard University Herbaria. 19 records from AMNH Mammal Collections. 19 records from Crustacea collection of National Museum of Nature and Science. 30 records from AMNH Herpetology Collections. 3 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 32 records from UMMZ Herpetology Collection. 1 records from Herbarium Specimens of Bonin and Ryukyu Islands. 10 records from TNHC Herpetology Collection. 2 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 1 records from Mammal specimens. 2 records from Natural History Museum, Vienna - Herbarium W. 8 records from Herbarium Berolinense. 18 records from RBINS collections. 1 records from Recent Invertebrates Specimens. 25 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Birds collection of Yamashina Institute for Ornithology. 53 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1 records from University of Vienna, Institute for Botany - Herbarium WU. 1 records from Naturalis Biodiversity Center (NL) - Botany Wageningen. 10 records from Collection Aves (spirit preserved) SMF. 1 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 56 records from Botany (UPS). 5 records from Field Museum of Natural History (Botany) Seed Plant Collection. 2 records from HSU Wildlife Birds. 4 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 238 records from herpetology. 131 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 15 records from CAS Invertebrate Zoology (IZ). 22 records from The System-wide Information Network for Genetic Resources (SINGER). 8 records from Collection Cnidaria SMF. 1 records from Lund Botanical Museum (LD). 2 records from UCM Amphibians and Reptiles. 5 records from Arizona State University Amphibian and Reptile Collection. 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 923 records from MAL. 2 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1077 records from EOD - eBird Observation Dataset. 10 records from AUM Fish Collection. 8 records from Spider Mites Collection of Jean Gutierrez. 1 records from Generic Taxonomic Database System on Mysida and Nematoda. 17 records from Fish collection of National Museum of Nature and Science. 22 records from Queensland Museum provider for OZCAM. 80 records from AntWeb. 1 records from UMZC Zoological Specimens. 1 records from mammals. 26 records from Diveboard - Scuba diving citizen science observations. 1 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 140 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 3 records from Naturalis Biodiversity Center (NL) - Mammalia. 1 records from KUBI Ornithology Collection. 41 records from NSW herbarium collection. 159 records from Naturalis Biodiversity Center (NL) - Mollusca. 2 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 21 records from United States National Plant Germplasm System Collection. 67 records from Geographically tagged INSDC sequences. 3 records from Fungi (S). 80 records from Collection Mollusca SMF. 7 records from WFVZ Bird Collections. 1 records from Database of Fungal Specimens Maintained at the Selected Japanese Herbaria. 58 records from CM Herps Collection. 9 records from Australian National Herbarium (CANB). 2 records from UTEP Vertebrates. 20 records from Collection Crustacea SMF. 326 records from LACM Vertebrate Collection. 2 records from Biologiezentrum Linz. 1 records from UWBM Ornithology Collection. 1 records from Mosses (S). 68 records from AMNH Bird Collection. 4 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 7666 records from NMNH occurrence DwC-A. 6 records from Northern Territory Museum and Art Gallery provider for OZCAM. 70 records from Natural History Museum (London) Collection Specimens. 3 records from DMNH Birds. 10 records from Nationaal Herbarium Nederland. 4 records from Flora of Japan Specimen Database. 6 records from HSU Wildlife Mammals. 4 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 11 records from Invertebrates (GBIF-SE:SMNH). 21 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 6 records from Collection Arachnology SMF. 20 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 7 records from South Australian Museum Australia provider for OZCAM. 5 records from Akita Prefectural Museum:Hiroki Watanabe Collection of mollusca. 1 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 36 records from invertebratezoology. 1 records from First Record of Eggplant Mealybug, Coccidohystrix insolita, (Hemiptera: Pseudococcidae), on Guam: Potentially a Major Pest. 8 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 32 records from Hexacoral Database. 1 records from SysTax - Zoological Collections. 5 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 21 records from KUBI Herpetology Collection. 1 records from International Fossil Shell Museum (NL) - Mollusca Collection. 81 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 2 records from Arizona State University Lichen Collection. 4 records from Herp specimens. 2 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 10 records from PRECIS. 1 records from Bishop Museum Data (OBIS distribution) (USOBIS). 3 records from Algae (S). 20 records from UTA Herpetology. 2 records from Bird specimens. 1 records from Lund Museum of Zoology - Insect collections (MZLU). 1 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 80 records from Australian National Insect Collection. 3 records from Collection Pisces SMF. 8 records from University of Alberta Entomology Collection (UASM). 22 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 21 records from NZFUNGI - Collections of the New Zealand National Fungal Herbarium (PDD). 53 records from Australia's Virtual Herbarium. 3 records from Field Museum of Natural History (Botany) Lichen Collection. 2 records from Bryophyte herbarium, Göttingen (GOET). 4 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 319 records from Australian Museum provider for OZCAM. 5 records from SDNHM Herpetology Collection. 7 records from Herpetology Collection. 6 records from Cryptogamy collection (PC) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1171 records from CAS Ichthyology (ICH). 628 records from Museum of Comparative Zoology, Harvard University. 1350 records from Fishbase. 137 records from KUBI Ichthyology Tissue Collection. 3 records from Naturalis National Natural History Museum (NL) – Crustacea_Decapoda.
Keywords: GBIF; biodiversity; species occurrences